Analysis of Islamic Boarding School Management in Improving Reading and Writing Literacy: Study of Pondok Pesantren Miftahul Ulum Putra, Gondanglegi, Malang - Fahrurrosi, Lingga; Husni, Muhammad (PT. Riset Press International, 2025)
This research is oriented to the management of Islamic boarding schools in improving students' literacy skills by reviewing the managerial process applied through 4 approaches, among others: planning (planning), organizing (organizing), actualizing (actuating), and evaluating (evaluating). The methodological knife used is qualitative with the research setting in the Miftahul Ulum Putra Islamic Boarding School, Gondanglegi, Malang. The technique of inputting data and information needed is done by interviewing the stakeholders concerned and accessing documents related to the object. This research was then compiled to critically and deeply analyze the Miftahul Ulum boarding school's management process in improving the students' literacy quality. Based on the research project that has been carried out, several results were found; first, the planning stage was carried out by offering several work programs aimed at improving the students' literacy skills. In the organizing stage, then from each work program that has been planned, a structure is formed based on the divisions that handle their respective fields. Furthermore, in the actualization stage, several existing activities have been carried out consistently, with a time allocation scheduled systematically and integrated with other boarding school activities. Meanwhile, for the evaluation, several obstacles were found, such as the division of the team through the existing divisions, each of which was very limited, the lack of active participants in participating in the planned series of activities, as well as problems in the internal management in the form of inactivity and maximization of the management concerned in carrying out their duties.